Multivariate Analysis of CO2 Emissions by Energy Generation in IEA Member Countries - Santos, Daiane; Barcellos de Carvalho Silva, Tuany Esthefany; Castro, Reinaldo Souza (Archives of Business Research, 2024)
The concentration of carbon dioxide (), the main catalyst for global warming, reached an average of 414.7 parts per million in 2021 and 2.3 ppm more than in 2020. This concentration of is the highest recorded in at least 800,000 years, according to the International Energy Agency. The increase in the concentration of is a growing concern in the scientific community and environmental organizations since the increase in global temperature resulting from this phenomenon can lead to serious and irreversible effects. This topic has gained space in global analyse and has become increasingly recurrent. This research aimed to deal with and analysed essential points in this discussion. With the study, it was possible to point out evidence that Brazil is a country that has been significantly reducing its emissions, being in the cluster along with IEA member countries that least issue . With this article, it was possible to point out similar characteristics between the emissions of the countries, making it possible to highlight three latent variables: countries that have a constant tall or low trend in emissions, Grouping of countries that showed an upward trend at the beginning of the analysed period, but with a significant reduction over time, and countries that have had more discrepant behaviour from the others, these being the countries that have a structural breakdown in their time series of emissions by power generation.